2011
DOI: 10.1242/dev.061481
|View full text |Cite
|
Sign up to set email alerts
|

The Cdk4-E2f1 pathway regulates early pancreas development by targeting Pdx1+ progenitors and Ngn3+ endocrine precursors

Abstract: SUMMARYCell division and cell differentiation are intricately regulated processes vital to organ development. Cyclin-dependent kinases (Cdks) are master regulators of the cell cycle that orchestrate the cell division and differentiation programs. Cdk1 is essential to drive cell division and is required for the first embryonic divisions, whereas Cdks 2, 4 and 6 are dispensable for organogenesis but vital for tissue-specific cell development. Here, we illustrate an important role for Cdk4 in regulating early pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 60 publications
6
46
0
Order By: Relevance
“…However, pRB and E2F family members can control neuronal and pancreatic development by direct regulation of genes such as Ngn3 (Kim and Rane 2011;Tsume et al 2012). Thus, E2F factors could orchestrate stem cell and progenitor differentiation in a diversity of tissues, underlining that cell cycle control of cell fate choice could be a common mechanism between a diversity of progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…However, pRB and E2F family members can control neuronal and pancreatic development by direct regulation of genes such as Ngn3 (Kim and Rane 2011;Tsume et al 2012). Thus, E2F factors could orchestrate stem cell and progenitor differentiation in a diversity of tissues, underlining that cell cycle control of cell fate choice could be a common mechanism between a diversity of progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…In a complementary experiment, mice lacking Cdk4 were shown to be relatively healthy with the notable exception of diabetes, due to depletion of pancreatic beta cells (30). More recently it was shown that Cdk4 acts at a very early stage in islet cell development by stimulating the replication of neuroendocrine stem cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attempted to increase endocrine, and particularly β-cell, proliferation through regulation of cell cycle proteins (37,38). Specifically, deletion of the cell cycle regulator Rb in differentiated β-cells did not significantly alter β-cell mass (22).…”
Section: Discussionmentioning
confidence: 99%